Khảo sát tình trạng ô nhiễm nước nuôi tôm tại công ty Thông Thuận, tỉnh Bình Thuận - Hoàng, Việt Hậu (Trường Đại học Đà Lạt, 2012)
In recent years, the development of aquaculture in Central South coast of Vietnam, especially shrimp farming has become an important economic sector. However, brackish media shrimp farming has been revealed many neagtive impacts to coastall ecology. Shrimp culturing in series without overall, as well as specific planning and compliance with technical applications has resulted in serious water pollution and outbreaks of diseases.